Replica arrangement for location dependent data in consideration of network partition in ad hoc networks. (22nd June 2009) - Tsuchida, Gen; Ishihara, Susumu
We propose link-aware and density based replica arrangement (LDR) method for dynamical arrangement of replicas of location dependent data that addresses the difficulties encountered by mobile hosts in ad hoc networks when trying to access data on other hosts due to the movement of hosts, obstacles, etc. In this LDR method, replicas of location dependent data items are placed on mobile hosts neighbouring branch points in the ad hoc network and the density of replicas is controlled in accordance with the degree of the network topology. Performance evaluation by simulation showed that the LDR method performs better than other methods when the requesting host is distant from the location where the target data item is associated and the host is moving quickly.